On the Torsion Units of Integral Adjacency Algebras of Finite Association Schemes. (16th December 2014) - Herman, Allen; Singh, Gurmail
Abstract : Torsion units of group rings have been studied extensively since the 1960s. As association schemes are generalization of groups, it is natural to ask about torsion units of association scheme rings. In this paper we establish some results about torsion units of association scheme rings analogous to basic results for torsion units of group rings.